Improvement of Heavy Oil Recovery by Nonionic Surfactant/Alcohol Flooding in Light of the Alkane Carbon Number and Interfacial Tension Properties - Alsabagh, Ahmad Mohamed (ACS Omega, 2021)
[Image: see text] In this work, we prepared nonionic surfactants from waste cooking oil materials. Hydrolysis was carried out for palm and palm kernel waste cooking oils to get a mixture of free fatty acids. The mixture of free acids was esterified with sorbitan and then ethoxylated at different ethylene oxide units. Two surfactants exhibited promising surface-active properties among the six prepared surfactants based on the results of surface tension. The interfacial tension (IFT) around the critical micelle concentration was measured against a series of n-hydrocarbon to detect the minimum alkane carbon number (ACN) (Π(min)) for each of these surfactants. The effect of normal and branched alcohols on Π(min) was also studied to design the surfactant/alcohol mixture for the chemical flooding process. From the results of IFT, the ethoxylated ester derivatives of palm kernel fatty acids (EPK-20) exhibited minimum IFT γ(min) (0.06 mN m(–1)) at Π(min) equal to 12, and the ethoxylated ester derivatives of palm fatty acids (EP-40) achieved γ(min) equal to 0.09 mN m(–1) at Π(min) of 10. Branched alcohols shifted Π(min) to a higher value to reach the equivalent ACN of the crude oil and decrease the IFT to lower values. The flooding process showed that the maximum oil recovery was obtained by EPK-20 (54.2% when used purely and 66.2% when used with isoamyl alcohol). In comparison, EP-40 exhibited that oil recovery equals 46% without alcohol and 46.4% with iso-butanol alcohol. The results were interpreted and discussed based on interfacial properties, wettability alteration, and the ACN.